1985
DOI: 10.1007/bf02389050
|View full text |Cite
|
Sign up to set email alerts
|

Nut cracking by wild chimpanzees in Sierra Leone, West Africa

Abstract: ABSTRACT. I report an incidence of chimpanzee (Pan troglodytes verus) cracking of Detarium senegalense (Caesalpiniaceae) At 16:35 chimps were observed leaving the area. The group included two adult females (one with a moderate sexual swelling, ca. 7 cm), one subadult or adult female, one medium size juvenile of indeterminate sex, and two large infants or small juveniles of indeterminate sex (one of these was carried piggyback by an adult female).Upon close investigation of the location at which the chimps we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…So far only chimpanzees and humans have been found to converge on the behaviour variant that is most common in the group, even if they have alternative behaviours in their individual repertoires that accomplish the same goal just as efficiently [67]. Conformist transmission has been proposed to restrict the accumulation of traditions in non-human [27,37,49] and human [62,68] populations. Therefore, local differences between populations remain despite individual exchange through marriage and migration [69], preventing cross cultural homogenization but protecting cultural diversity among neighbouring communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far only chimpanzees and humans have been found to converge on the behaviour variant that is most common in the group, even if they have alternative behaviours in their individual repertoires that accomplish the same goal just as efficiently [67]. Conformist transmission has been proposed to restrict the accumulation of traditions in non-human [27,37,49] and human [62,68] populations. Therefore, local differences between populations remain despite individual exchange through marriage and migration [69], preventing cross cultural homogenization but protecting cultural diversity among neighbouring communities.…”
Section: Discussionmentioning
confidence: 99%
“…Chimpanzees in the wild are known to use natural stone and wooden hammers to crack open various nut species [14,30,[36][37][38][39][40]. Nut-cracking is a classic percussion behaviour whereby a nut is placed on a hard surface and a hammer is used to pound it until the nut breaks open.…”
Section: Introductionmentioning
confidence: 99%
“…Nut-cracking behaviour has been directly observed in several populations of chimpan zees [Boesch and Boesch, 1981, 1983, 1984Sugiyama and Roman, 1979;Sugiyama, 1981;Whitesides, 1985], and some studies have been conducted on the acquisition and dissemination of this behaviour both in a captive group [Sumita et al, 1985] and in captive chimpanzees released on a natural island in Liberia [Hannah and McGrew, 1987], Data on wild chimpanzees show that 'the ontogenesis of nut cracking is a longerlasting process than that of the other tool techniques used by chimpanzees' that are acquired years earlier [Boesch and Boesch, 1984, p.436]. Furthermore, Beck [1980, p. 100] notes that nut-cracking has rarely been reported for captive chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…T ool use among modern wild ape populations, first reported in the early 19th century (1), has been documented throughout tropical Africa, and chimpanzees from West Africa are known for their use of stone tools for nut cracking (2)(3)(4)(5)(6). In 2002, the publication of recent buried remains of unintentionally fractured stone left behind by modern chimpanzees from Côte d'Ivoire outlined the potential of using archaeological methods in cultural primatological research and also identified the type of material assemblage that would allow archaeologists to detect and characterize ancient chimpanzee nut-cracking behavior.…”
mentioning
confidence: 99%